Akibat Hukum Penentuan Nasib Sendiri Menurut Hukum Internasional (Kasus Di Papua Barat) - Pollatu, Maretz; Wattimena, Josina Augustina Yvonne; Waas, Richard Marsilio (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Legal independence by contract in international law is a form of self-deception (the right to self-determination), so that self-deception is a right that must also be emphasized more so that countries can follow it. Purposes of the Research: The purpose of this writing is to study and find out the legal consequences according to international law (the case in West Papua).Methods of the Research: This study uses a normative juridical method with the legal materials used in the research being primary, secondary and tertiary and the procedure and analysis of legal materials in the research through the process of collecting legal materials then studied, read, studied, classified, and analyzed qualitatively.Results of the Research: The legal consequences of the problem regarding Benny Wenda's statement are not in accordance with international law so that the legal consequences are faded towards a certain legal situation because the State of Indonesia is a sovereign country through the process of fighting for human rights and state values based on democratic references.